1991
DOI: 10.1177/000348949110000912
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma in an Inverted Papilloma of the Buccal Mucosa

Abstract: Inverted papillomas of the oral cavity are rare lesions. Although in the seven oral cases previously reported the lesions were benign, approximately 10% to 15% of inverted papillomas of the nasal cavity and paranasal sinuses develop or are associated with squamous cell carcinoma. This report presents a case of squamous cell carcinoma arising in an inverted papilloma of the buccal mucosa. Histologically, this lesion demonstrated the morphologic features of inverted papilloma in the superficial portion, and squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The patient age at appearance of the lesion is usually between the fourth and fifth decade of life and no particular gender predilection has been observed (1,5). In our review of the literature, the mean age was found to be 44 years, with a range of 27-65 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient age at appearance of the lesion is usually between the fourth and fifth decade of life and no particular gender predilection has been observed (1,5). In our review of the literature, the mean age was found to be 44 years, with a range of 27-65 years.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative course in our patient was free of complications, and she is presently subjected to periodic controls to detect possible relapse. No relapses or malignization of IDPOC have been documented though a squamous cell carcinoma in an IP of the cheek mucosa has been identified (1). In most cases these complications are a consequence of an incomplete resection of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ectopic occurrence of schneiderian papillomas -that is, outside the sinonasal tract -has been reported in 15 patients. Three of these cases occurred in the nasopharynx, 7-9 2 in cervical lymph nodes, 10 -1 ' 1 in the oropharynx, 12 1 in the oral cavity, 13 1 in the hypopharynx, 14 and 7 in the middle ear and mastoid. 15 " 18 Five of the lesions of the middle ear and mastoid originated from the Otolaryngic Tumor Registry of the Armed Forces Institute of Pathology.…”
Section: Discussionmentioning
confidence: 98%